Gender and Social Justice in Urban Agriculture: The Network of Agroecological and Peripheral Female Urban Farmers from São Paulo - Laura Martins de Carvalho; Cláudia Maria Bógus (Social Sciences, 2020)
This article analyses women’s participation in the ‘Network of Agroecological and Peripheral Female Urban Farmers’, an agroecological urban agriculture grassroots network in São Paulo, Brazil. The methodology used was participant observation. The following procedures were used to produce the data: participation in three workshops, direct observation, field notes, and an in-depth interview with two of the organizers and three participants. The results show that the Network engendered the formation of a popular feminist collective identity, as it fostered the awareness of oppressive social structures, such as gender inequality and violence against women, of which many participants were survivors. From a technical standpoint, the Network seeks to expand its scope of action, increase the number of participants, establish new partnerships and access multiple sources of funding to obtain greater autonomy from São Paulo City Council.